PERBANDINGAN HASIL PEMBUBUTAN DENGAN MENGGUNAKAN MATA PAHAT KARBIDA DAN MATA PAHAT HSS DI BENGKEL POLMUH - Auly Fatkhur Hidayat; Muhamad Zainudin; Sudarmono (Yayasan Nusantara Hasana Berdikari, 2023)
In the fast-paced period, human desire to produce and compete quickly, efficiently and economically, became the basis for the development of tools and machine tools, the competition provided the main motivation in making machine tools that have accuracy, accuracy and precision, so as to make shape in accordance with the design (model). So in this case what should be considered is how to choose and determine the tool material to be used on a lathe, because it can affect the level of wear on the tool eye itself and the fineness or surface roughness that will be generated can be controlled visually. Comparing the use of carbide chisel with HSS chisel to eat ST 37 steel workpieces, in this study aims to determine the use of chisel blade in order to produce smooth workpiece surface fibers and have a small degree of roughness visually in the turning process of steel workpieces ST 37. The results of testing the use of carbide chisels produce finer surface fibers and visually smaller roughness than HSS chisels, so if you turn the ST 37 steel workpiece you should use carbide chisels to get good results.